DALIHAN NA TOLU DI RANTAU: KAJIAN PERUBAHAN DAN REKONSTRUKSI NILAI- NILAI DALIHAN NA TOLU PADA GENERASI MUDA IKATAN BATAK MUSLIM (IKABAMUS) LAMPUNG - Yusrina, Yusrina; Nurdin, Bartoven Vivit (SOCIOLOGIE, 2013)
Dalihan Na Tolu is dealt live in culture that governs the relationship of family, as well as the Customs already underway hereditary which is sustained by the three powers, namely, the hula-hula, boru, dongan sabutuha. This research aims to clarify the meaning of the analysis Dalihan Na Tolu for, examines the changes and Dalihan Na Batak Tolu in Lampung. And reconstruction Dalihan Na Tolu IKABAMUS Lampung. The type of research used in this study is a qualitative method of data collection, observation and in-depth interview study documentation Technique of data analysis performed by reduction of data, presentation of data, conclusion and withdrawal. From the results of the study showed that Dalihan Na Tolu is experiencing changes that are affected by assimilation and acculturation. covert culture as a system of values is the identity (surname) and has a patrilineal people are both difficult to change. Religious beliefs in the Batak had a set according to the custom of Dalihan Na Tolu but still clinging to religion. In the Batak have some whove studied customs such as partuturan, and some custom functions that netted in the community such as Hula-hula function, boru, and dongan sabutuha. While the overt culture of physical culture, as for example the tools and objects that are useful in the Batak have objects they deem useful as ulos, science began to change as it is affected by technology and innovation, the procedures/lifestyle they are brought together to attempt to revive the Dalihan Na Tolu return to youth is done by involving youth about traditional Batak.Keywords: Change dalihan na tolu, IKABAMUS, reconstructions